Custom Slipcovers Made Easy - Dubicki, Elizabeth; Edited by Conradt, Tracy L. (Lola WI F+W Publications, 2007)
A complete guide to creating custom slipcovers to suit any type of decor presents a full range of stylish projects designed to transform flea market or garage sale finds into designer originals, with instructions, accompanied by more than two hundred photographs, for twenty-five furniture coverings for chairs, love seats, sofa sleepers, and more.
Include Colour Illustrations
Designed by Bittner-Zastrow, Heidi